Venezuela : Fiction in the Dark - Alvarado, Morella; Torrealba, Luisa (Obitel 2020: Melodrama in Times of Streaming, 2020)
During 2019, various situations once again showed the deep crisis in the country. Audiovisual production continued, albeit with figures that account for a declining industry. Four productions were released: a first was made by the state channel (TVe), a second by a local independent producer (Oduver Cubillán and BGcreativos), the third was produced by the private channel (RCTV) and broadcast by the subscription channel IVC Networks, and the fourth was also produced by RCTV. While the first two productions did not exceed the 35-episode figure, the third and fourth had 73 episodes. On March 7, there was the biggest blackout in the country’s history. For more than a week, 95% of the territory was paralyzed by a lack of electricity. The action was classified by the government as an electric sabotage. The darkness that covered the country also subsumed serial fiction.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Venezuela (corpus analysé); Venezuela (lieu de production du savoir); _Nettoyé

Uruguay: Ibero-American Fiction Loses Ground to Entertainment - Sánchez Vilela, Rosario; Gadea, Lucia (Obitel 2020: Melodrama in Times of Streaming, 2020)
A look at the screens of Uruguay’s open television in prime time will give the viewer a very reduced offer: after a television newscast that exceeds two hours long, there are only contest pro- grams, national or imported ones. It is possible that in the afternoon and at night the viewer finds a telenovela, almost always Turkish one. This is a very different panorama from the Uruguayan televi- sion history. Ibero-American fiction is in decline on open television, while its offer on VoD expands. In this chapter we will try to consider the various aspects of this landscape. Melodrama is on both options, open television and streaming, on a broad thematic spectrum, even in productions that are not usually classified as such. In the absence of national fiction in the period, at the end of the chapter we will study the melodrama in prison fiction, particularly in the case of El Marginal.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Uruguay (corpus analysé); Uruguay (lieu de production du savoir); _Nettoyé

Peru: Social Issues and Comedy in Fiction - Cassano, Giuliana; Vásquez, Guillermo; Dettleff, James A. (Obitel 2020: Melodrama in Times of Streaming, 2020)
The country’s political crisis led to the confrontation between the Peruvian Congress and President Martín Vizcarra on irreconcil- able limits. After a second denial of confidence, Vizcarra made use of his constitutional prerogatives and dissolved Congress at the end of September 2019. The majority of the mass media step in line with the different positions of the Executive or the opposition, giv- ing much more attention to the political situation, thus modifying the TV programing. In this scenario, the Enfoca group – owner of Latina station – has continued looking for potential buyers, but without success yet. The conglomerate – with interest in financial, health and productive sectors – does not feel that the investment made in acquiring all the station’s shares seven years ago yielded the expected results. Meanwhile, Willax – a small locally held station acquired by the Wong group in 2015 with promises of a large investment – has become a stronghold of opposition to the government of Vizcarra and the largest broadcaster of Korean fictions. In February 2020, they an- nounced that a commercial partnership had been signed with South Korean company CJ ENM, a production company of several Korean dramas and the award-winning film Parasite, but without indicating what this company could mean for audiovisual production in Peru.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Pérou (corpus analysé); Pérou (lieu de production du savoir); _Nettoyé

Colombia: Melodrama Lives in Times of Streaming - Díaz, Fernando Aranguren; Bohórquez, Borys Bustamante; Riveros Solórzano, Hernán Javier (Obitel 2020: Melodrama in Times of Streaming, 2020)
The year 2019 in Colombia was characterized by the presence of a series of social and cultural phenomena of high impact on the population, such as the National Strike on November 21, when dif- ferent sectors expressed their disagreement with the country’s poli- cies and the reforms that were being proposed for the new year. This situation led to a leading presence of the news on the small screen and, at the same time, an interesting reflection of national identity, the needs of various Colombian social groups and the cul- tural matrices of the nation. In this hectic context and in accordance with a certain global climate of crisis in democratic and government systems, a highly interesting television phenomenon emerges: the highly successful reappearance of the programs that marked differ- ent generations of compatriots and that, as in the past, once again led families to discuss episodes and situations presented under the classical structure of melodrama.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); Colombie (corpus analysé); Colombie (lieu de production du savoir); _Nettoyé

Brazil: Time of Brazilian Streaming - Vassallo de Lopes, Maria Immacolata; Prezia Lemos, Ligia (Obitel 2020: Melodrama in Times of Streaming, 2020)
In 2019, the World Wide Web (www) celebrated its 30th anni- versary, However, the internet had not yet asserted itself as a right in the “network society” (Castells, 2009), and its balance points to the expansion of both opportunities and threats. Another fact that deserves to be highlighted in the year was the drop in the rating as a global phenomenon that challenges the television industry. It means change of habits and search for new business models. The integration of platforms and the generation of quality content appear as pillars of thetransformation of audiovisual worldwide. And the changes are manifested with a certain degree of diversity, according to the economic and cultural characteristics of each society, with disruptive processes.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Brésil (corpus analysé); Brésil (lieu de production du savoir); _Nettoyé

Argentina: The Fall of Open TV Continues: Production Companies Bet on Platforms with Themes Regarding Marginality and Corruption - Aprea, Gustavo; Kirchheimer, Mónica S.; Rivero, Ezequiel A. (Obitel 2020: Melodrama in Times of Streaming, 2020)
Serial fiction released in Argentina in 2019 continues to fall. Only one telenovela had more than 200 chapters. To a lesser extent than the previous year, the supply of serialized fiction incorporated themes from the social agenda, especially feminist struggles and the visibility of sexual dissidence. The channels found in the co-produc- tion and in the production for platforms one of the ways in which fic- tion survives. Some of these programs are now on the open television screen. New fiction releases from Ibero-America are also falling.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Argentine (corpus analysé); Argentine (lieu de production du savoir); _Nettoyé

Manuel Zapata Olivella, le muntu africain et la décolonisation des imaginaires et des épistémologies en Amérique Latine - Akassi, Clément Animan (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2019)
Ce travail vise à montrer deux choses. La première, c’est de saisir toute l’importance du tournant postcolonial/afro-décolonial dans la construction d’une contre-épistémologie propre au sujet culturel colonisé africain. En d’autres termes, pour le sujet colonisé, cette contre-épistémologie sert à décoloniser les imaginaires, à partir d’un questionnement de la colonialité de l’épistémologie et du savoir donnés pour universels par l’occident. La deuxième chose, c’est que ̶ à quelques mois de la commémoration du centenaire de la naissance du prolixe et polygraphe auteur africain-colombien Manuel Zapata Olivella (1920-2004) ̶ cet article puisse le situer à sa juste place. Celle d’un sujet culturel colonisé africain des Amériques dont l’abondante production culturelle et la pensée, portées et révolutionnées par le concept de Muntu africain, participent de la décolonisation des imaginaires et de l’épistémologie
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas--from Nunavut to Tierra del Fuego. Through three themes--landscape, territory, and trade--this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."--Résumé de l'éditeur
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Equivocation, Translation, and Performative Interseccionality: Notes on Decolonial Feminist Practices and Ethics in Latin America - de Lima Costa, Claudia (ANGLO SAXONICA, 2013)
In this paper I offer a brief overview of the academic debates about post-colonial theories and the concept of coloniality, seeking to map out their Latin American translations, especially from the perspective of feminist theories in relation to the coloniality of gender. By emphasizing an intersectional approach to understand the gendered character of coloniality, decolonial feminists are seeking innovative ways of articulating new epistemologies or “saberes propios”. However, in these debates little attention has been given to the issue of the travels and translations of decolonial feminisms in Latin America. In focusing on the vexed issue of translation, I want to explore some of the challenges Latin American decolonial feminists are facing today.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Cuerpos in/a-propiados: carte-de-visite y las nuevas ciudadanias en la pardocracia venezolana postindependentista - González-Stephan, Beatriz (Memoria y Sociedad, 2013)
En medio del proceso de construcción de la República, durante el siglo xix, en Venezuela los sectores no blancos de la sociedad intentaron legitimarse a través de la fotografía en las carte-de-visite, con el objetivo de ratificar su posición en esta sociedad ‘café con leche’. El uso de esta tecnología, así como la aparición y aceptación de manuales de urbanidad, fueron parte de un proceso en el que estos sectores intentaron ‘modernizarse’, reflejando las tensiones sociales asociadas, por ejemplo, a la dicotomía campo-ciudad o a la necesidad de ‘blanquearse’ ante los ojos de los coterráneos. El objetivo de este trabajo, es estudiar la manera en que el retrato fotográfico y el manual de urbanidad actúan en una sociedad cuyas diferencias y distancias sociales y económicas han sufrido un gran trastorno luego del proceso independentista. During the process of the construction of the Republic, in the 19th Century, non-white sectors of Venezuelan society attempted to legitimise themselves through photographs in their cart-de-visite, with the object of ratifying their position in this ‘coffee and milk’ society. The use of such technology, as well as the introduction and acceptance of urbanity handbooks, were part of a process in which these sectors tried to ‘modernise’, reflecting related social tensions, for example, the urban-rural dichotomy or the need for ‘whitening’ themselves in the eyes of their fellow citizens. The purpose of this paper is to study the way in which photographic portraits and urbanity handbooks act in a society in which social and economic differences and distances have undergone a great upheaval since the independence process.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Representaciones del espacio, el tiempo y las mujeres indígenas en fotografías, siglos XIX-XXI - Yujnovsky, Ines (Memoria y Sociedad, 2017)
Este trabajo se propone comprender la incidencia de las relaciones de poder que ciertas representaciones temporales acerca de grupos indígenas pueden ejercer en nuestra comprensión pasada y actual. Diversas imágenes reprodujeron ideas de indígenas que, aunque estuvieran vivos, mostraban una cultura asimilada a un pasado de amplias dimensiones. Por lo tanto, para comprender el proceso de invisibilización de la diversidad indígena en la cultura nacional, es relevante considerar los mecanismos de montaje discursivo —visuales y textuales—, vinculados con las nociones temporales de indios viviendo en un supuesto tiempo remoto. Atendiendo a ello, se analizan los procesos de montaje, desde la producción de las fotografías hasta la edición y presentación de imágenes, tanto en la prensa como en postales, publicaciones científicas y de divulgación, para ver cómo a veces pequeños cambios de encuadre, contraste, retoque o selección pueden incidir en la construcción de diversas historias, en la comprensión y en los sentidos construidos y en pugna.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Imágenes de lo extraordinario. Memorias de un continente poblado por monstruos. - Gil, Slenka Leandra Botello; Camacho, Daianna Sierra (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
Este trabajo presenta los resultados de la investigación Imágenes de lo extraordinario: monstruos americanos del siglo XVI, proceso de creación artística desarrollado por los estudiantes del Semillero de Investigación en Artes Visuales (SINAV) del programa de Artes Visuales de la Universidad Nacional Abierta y a Distancia (UNAD) entre 2018 y 2019. Para analizar de manera crítica e histórica la construcción de identidades sobre lo latinoamericano, se tomó como marco de análisis la representación de lo monstruoso en los relatos y las imágenes construidas por los cronistas de Indias en el siglo XVI, los cuales marcaron procesos de marginalización cultural, construcción de subjetividades y dinámicas de poder, y presentaron al habitante americano como una otredad que estaba fuera de los límites de la cultura dominante occidental. Se presentan los postulados teóricos sobre lo monstruoso como marco para el análisis histórico y la creación de obra, con una metodología de trabajo colaborativo y en gran parte virtual. Posteriormente, se exponen algunos resultados de la investigación histórica que dan paso a detallar el proceso de creación de obra que culminó con la exposición de la instalación audiovisual Imágenes de lo extraordinario, así como con una amplia serie de ilustraciones contemporáneas sobre lo monstruoso y un producto digital en formato página web donde se presenta una cartografía de lo monstruoso en América Latina y se recogen las memorias de todo el proyecto. This work presents the results of the research Images of the Extraordinary: American Monsters of the 16th Century, artistic creation process developed by the students of the Research Seedbed in Visual Arts (SINAV, for its initials in Spanish) of the Visual Arts program of Universidad Nacional Abierta y a Distancia (UNAD) between 2018 and 2019. With the objective of analyzing, in a critical and historical way, the construction of identities on Latin American matters, the representation of the monstrous in the stories and images constructed by the chroniclers of the Indies in the 16th century was used as a framework of analysis. These chroniclers marked processes of cultural marginalization, construction of subjectivities and power dynamics, and presented the American inhabitant as an otherness that was outside the limits of the dominant Western culture. The theoretical postulates about the monstrous are presented as a framework for historical analysis and the creation of works, with a collaborative and largely virtual working methodology. Some results of the historical research are then presented, which gives way to detailing the process of creating work that culminated in the exhibition of the audiovisual installation Images of the Extraordinary, as well as a wide range of contemporary illustrations on the monstrous and a digital product in web page format where a cartography of the monstrous in Latin America is presented and the memories of the whole project are collected.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Memorias americoafricanas en el trabajo de artistas brasileñas contemporáneas - Sardelich, Maria Emilia; Cao, Marian López Fernandez (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
La memoria hace referencia a un conjunto de funciones psíquicas que permiten la actualización de imágenes de hechos pasados o que se representan como pasados. A diferencia de los estudios históricos, los de la memoria resaltan las subjetividades, amplían la discusión más allá del recuerdo y el olvido, y desplazan el debate hacia quien tiene el derecho a narrar su historia y aquellos que en ella se encuentran. Las inquietudes en torno a la memoria y sus lugares también se hacen visibles en el inquieto horizonte artístico, en el que pasados recientes y distantes se articulan en registros sobre diversas formas de traumas. Este artículo propone una reflexión sobre las relaciones entre arte y memoria a partir de la producción de dos artistas brasileñas contemporáneas: Rosana Paulino (São Paulo, 1968) y Aline Motta (Niterói, 1974). El análisis de esa producción se fundamenta en la interdisciplinaridad de los estudios de la memoria y destaca cómo la creación artística ofrece una posibilidad de resignificación individual y colectiva. Asimismo, conceptúa memorias americoafricanas como aquellas que emergen no solo en la memoria individual de las artistas presentadas en este artículo, sino también en la de muchas otras mujeres que se identifican con Americoáfrica como un sistema etnogeográfico de referencia. Son memorias americoafricanas porque se han gestado en la resistencia y creatividad contra la opresión, la humillación y la deshumanización, y que se insurgen contra la historia única proponiendo una revisión de la historiografía del país y del arte producido a partir de esos lugares. Memory refers to a set of psychic functions that allow the updating of images of past events or events that are represented as past. Unlike historical studies, memory studies highlight subjectivities, expand the discussion beyond memory and oblivion, and shift the debate towards who has the right to narrate their history and those who are in it. The concerns about memory and its places also become visible in the restless artistic horizon, in which recent and distant pasts are articulated in registers about various forms of trauma. This paper proposes a reflection on the relationship between art and memory based on the production of two contemporary Brazilian artists: Rosana Paulino (São Paulo, 1968) and Aline Motta (Niterói, 1974). The analysis of this production is based on the interdisciplinary nature of memory studies and highlights how artistic creation offers a possibility of individual and collective resignification. Likewise, it conceptualizes African-American memories as those that emerge not only in the individual memory of the artists presented in this article, but also in that of many other women who identify with Africa-America, as a reference ethnogeographic system. They are African-American memories because they have been born in resistance and creativity against oppression, humiliation and dehumanization, and because they insurrect against the unique history, proposing a review of the historiography of the country and the art produced out of those places.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

Cuerpo, género y representación en el videoarte ecuatoriano (1998-2012) - Mantilla, Christian León (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2016)
Este texto reflexiona sobre los discursos e imaginarios de género y sexualidad que se producen dentro del campo del videoarte realizado en Ecuador entre 1998 y 2013. Desde finales de los noventa, hay una presencia de videos que abordan temáticas de cuerpo, política, deseo, violencia, roles e identidad que posicionan nuevos temáticas, lugares de enunciación y sujetos través de las tecnologías de video. A través de un conjunto de obras emblemáticas, el texto analiza los discursos y las estrategias visuales con las cuales se construyen feminidades, masculinidades y diversidades sexuales en el contexto contemporáneo. Está producción plantea un relato alternativo frente a las tendencias dominantes dentro de la historia del arte ecuatoriano. Muestra las nuevas sensibilidades y sujetos que se afirman a través del uso de tecnologías de video. This paper reflects on the speeches and imaginary of gender and sexuality that occur within the field of video art made in Ecuador between 1998 and 2013. Since the late nineties, there is a presence of vid-eos that address issues of body politics, desire, vio-lence, roles and identity that position new themes, places and subjects of enunciation through video technologies. Through a set of emblematic works, the text analyzes the speeches and visual strategies which femininity, masculinity and sexual diversities are built in a contemporary context. This production presents an alternative story against the dominant trends in the history of Ecuadorian art. It shows the new sensibilities and subjects that are affirmed through the use of video technology.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

Shekuita o el mal trueno: documental performativo, conflictos ontológicos y descolonización de lo real - Rincón, Juan Carlos Valencia; Hoyos, Paula Andrea Restrepo (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
Este artículo analiza las implicaciones ontológicas y el carácter performativo del documental Shekuita o el mal trueno, lanzado en 2017 por un colectivo de producción audio- visual indígena wiwa en la Sierra Nevada de Santa Marta en Colombia. El documental explora las causas, dudas y consecuencias de un triste incidente ocurrido tres años antes: la caída de un rayo sobre una edificación ceremonial de los wiwas, que causó la muerte a casi una docena de líderes. A partir del contraste entre las explicaciones científicas de la tragedia y las que han investigado las autoridades espirituales de la comunidad desde sus ontologías relacionales, y basándonos en un trabajo de campo cuasietnográfico durante el proceso de filmación, buscamos dar cuenta de un caso específico de descolonización de lo real y de los esfuerzos de una comunidad indígena por la libre expresión y la representación autónoma. Encontramos que este documental abre puertas de forma artística a mundos otros, contados en clave insumisa desde una indigenidad que nos interpela. Concluimos que los wiwas performan un realidad que no necesariamente es la que vivieron, sino una que les permite estratégicamente alcanzar más fácilmente la realidad que quieren recuperar. El artículo intenta contribuir a la visibilización de otras ontologías distintas de la naturalista, a mostrar las autocríticas de esta y a manifestar cómo el audiovisual es un espacio propicio para descolonizar lo real. This paper analyzes the ontological implications and the performative nature of the documentary Shekuita o el mal trueno, released in 2017 by a Wiwa indigenous audiovisual production group in Sierra Nevada de Santa Marta, Colombia. The do-cumentary explores the causes, doubts and consequences of a sad incident that happened three years earlier: a lightning strike on a Wiwas ceremonial building, which killed nearly a dozen leaders. Based on the contrast between the scientific explanations of the tragedy and those that the spiritual authorities of the community have investigated according to their relational ontologies and based on a quasi-eth-nographic fieldwork during the filming process, we seek to account for a specific case of decolonization of reality and of the efforts of an indigenous community for free expression and autonomous representation. We find that this documentary opens doors to other worlds in an artistic way, told in an unsubmissive way by an indigenous community that challenges us. We conclude that the Wiwa perform a reality that is not necessarily the one they lived through, but one that strategically allows them to reach the reality they want to recover more easily. The paper at-tempts to contribute to the visibility of other ontologies other than the naturalistic one, to show self-criticism of it and to show how the audiovisual is a propitious space to decolonize reality.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Marta Rodríguez, descolonizando la representación documental latinoamericana - Moreno, Pedro Pablo Gómez (Estudios Artísticos, 2017)
En esta conversación entre la cineasta documental Marta Rodríguez y Pedro Pablo Gómez, antes que hacer un recorrido cronológico por el trabajo la artista, se abordan problemas tranversales que están presentes a lo largo de su obra: el cine documental como modo de representación; la construcción de una metodología del cine documental latinoamericano; el carácter decolonial de la obra de Rodríguez y su compromiso indeclinable durante más de cuatro décadas de acompañar las luchas de campesinos, indígenas y afrodescendientes, entre otros. Y es en este abordaje donde Marta Rodríguez, haciendo uso de una memoria extraordinaria, puede tejer un relato en el que se destaca la ética de la artista y su compromiso indeclinable de denuncia de las injusticias sociales, utilizando las tecnologías del cine, no para hablar por las víctimas, sino para hacer escuchar sus voces y mantener vivas sus imágenes; unas imágenes que interpelan el discurso colonial mediante el cual se ha tejido nuestro relato de nación. Dans cette conversation entre la cinéaste documentaire Marta Rodríguez et Pedro Pablo Gómez, avant d'entreprendre une tournée chronologique de l'œuvre de l'artiste, nous traitons les problèmes transversaux présents tout au long de son travail : le cinéma documentaire comme mode de représentation ; la construction d'une méthodologie du documentaire latino-américain; la nature décoloniale de l'œuvre de Rodríguez et son engagement pendant plus de quatre décennies pour accompagner les luttes des paysans, des indigènes et des Afro-descendants, entre autres. Et c'est dans cette approche que Marta Rodríguez, avec une mémoire extraordinaire, peut tisser une histoire qui souligne l'éthique de l'artiste et son engagement indécelable à dénoncer les injustices sociales, en utilisant les technologies du cinéma –pour ne pas parler en lieu des victimes, mais pour faire entendre leur voix et garder leurs images vivantes. Des images qui contestent le discours colonial par lequel notre récit de nation a été tissé.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Recherche-création; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créatrice; _Nettoyé

Feminism in Play - Gray, Kishonna L.; Voorhees, Gerald; Vossen, Emma (Palgrave games in context, 2018)
Feminism in Play focuses on women as they are depicted in video games, as participants in games culture, and as contributors to the games industry. This volume showcases women's resistance to the norms of games culture, as well as women's play and creative practices both in and around the games industry. Contributors analyze the interconnections between games and the broader societal and structural issues impeding the successful inclusion of women in games and games culture. In offering this framework, this volume provides a platform to the silenced and marginalized, offering counter-narratives to the post-racial and post-gendered fantasies that so often obscure the violent context of production and consumption of games culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Critical media studies, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Hacia una memoria decolonial: breves apuntes para indagar por el acontecimiento detrás del acontecimiento fotográfico - Schlenker, Alex (Revista de Investigación en el Campo del Arte, 2012)
El retrato ha sido, a lo largo de la historia de la fotografía, un ritual cuya gramática visual está siempre condicionada por una mirada determinada. Retratamos para recordar, para fijar un instante en el tiempo. Cuando recordamos lo fotografiado convocamos de nuevo ese instante, pero, además, convocamos una realidad, un orden social específico construido por determinados actores sociales. La fotografía ha representado y legitimado en muchos momentos un patrón de poder colonial que, a través de sus estructuras de dominación, ha elaborado rígidas jerarquías sociales y raciales que han circunscrito a indios, afros, mujeres y clases populares a lo que Frantz Fanon llama la zona del No-ser. ¿Es posible recordar, entonces, a partir de la fotografía, de manera crítica y sin reproducir en tal ejercicio la matriz colonial que hizo posible la toma de la imagen?
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé